2016
DOI: 10.1016/j.foodchem.2016.02.059
|View full text |Cite
|
Sign up to set email alerts
|

Retrogradation behavior of corn starch treated with 1,4-α-glucan branching enzyme

Abstract: The retrogradation behavior of corn starch treated with 1,4-α-glucan branching enzyme (GBE) was investigated using rheometry, pulsed nuclear magnetic resonance (PNMR), differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR). Dynamic time sweep analysis confirmed that the storage modulus (G') of corn starch stored at 4 °C decreased with increasing GBE treatment time. PNMR analysis demonstrated that the transverse relaxation times (T2) of corn starches treated with GBE were hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(65 citation statements)
references
References 40 publications
5
60
0
Order By: Relevance
“…Among 803 CAZymes, 24 were involved in starch degradation, while 5 to 21 were found in the other 10 investigated filamentous fungi (see Supplementary Table S6). These 24 enzymes were composed of 5 α-amylases (EC 3.2.1.1), which mainly break internal α-1,4-glucosidic linkages and some branched α-1,6-glycosidic linkages from the inner starch chain; 13 α-glucosidases (EC 3.2.1.20), which break α-1,4-linkages in mainly maltose and short maltooligosaccharides to release glucose at nonreducing ends 27 ; 5 glucoamylases (EC 3.2.1.3), which mainly hydrolyze α-1,4-glucosidic linkages from the nonreducing ends of starch chains with the release of β-D-glucose 28 ; and a 1,4-α-glucan branching enzyme (EC 2.4.1.18) that cleave α-1,4 glucosidic linkages of glucan chain, and then transfer the cut end to 6-position of glucose residue within the cleaved or another glucan chain, resulting the generation of an α-1,6 glucosidic linkage 27, 29 . Comparative analysis indicated that T .…”
Section: Resultsmentioning
confidence: 99%
“…Among 803 CAZymes, 24 were involved in starch degradation, while 5 to 21 were found in the other 10 investigated filamentous fungi (see Supplementary Table S6). These 24 enzymes were composed of 5 α-amylases (EC 3.2.1.1), which mainly break internal α-1,4-glucosidic linkages and some branched α-1,6-glycosidic linkages from the inner starch chain; 13 α-glucosidases (EC 3.2.1.20), which break α-1,4-linkages in mainly maltose and short maltooligosaccharides to release glucose at nonreducing ends 27 ; 5 glucoamylases (EC 3.2.1.3), which mainly hydrolyze α-1,4-glucosidic linkages from the nonreducing ends of starch chains with the release of β-D-glucose 28 ; and a 1,4-α-glucan branching enzyme (EC 2.4.1.18) that cleave α-1,4 glucosidic linkages of glucan chain, and then transfer the cut end to 6-position of glucose residue within the cleaved or another glucan chain, resulting the generation of an α-1,6 glucosidic linkage 27, 29 . Comparative analysis indicated that T .…”
Section: Resultsmentioning
confidence: 99%
“…2 and Table 3, which indicates that the T 2 relaxation times of the starch gels change with different storage temperatures. When brought to 25 AE 0.1°C, the T 2 values of the gels stored at À20°C were the largest, suggesting that the water mobility was the highest (Li et al, 2016). This condition might be attributed to the fact that the gels went through the zone of maximum ice crystal formation (À1 to À5°C) and formed 'sponge' structures (Wang et al, 2010), and water molecules flowed out easily once they were brought to room temperature.…”
Section: Lf-nmr Spin-spin Relaxation Times (T 2 )mentioning
confidence: 98%
“…The distribution of T 2 relaxation times of (MS) and (MS-FG) gels is shown in Fig. When brought to 25 AE 0.1°C, the T 2 values of the gels stored at À20°C were the largest, suggesting that the water mobility was the highest (Li et al, 2016). When brought to 25 AE 0.1°C, the T 2 values of the gels stored at À20°C were the largest, suggesting that the water mobility was the highest (Li et al, 2016).…”
Section: Lf-nmr Spin-spin Relaxation Times (T 2 )mentioning
confidence: 99%
“…During the gelatinized dispersion of starch stored at low temperature, a loose paste or gel would form, and this phenomenon was depended on the starch concentration. In the present study, a 3Dnetwork gel was achieved through the rearrangement of starch molecules, with the phenomena that G ′ predominated over G ″ . The short‐term development of the gel structure was generated from the reordering and crystallization of amylose, which was attributing to the leaching out from the starch granules.…”
Section: Resultsmentioning
confidence: 70%
“…For the dynamic time scan, the fully gelatinized samples were maintained at 4 °C for 1 min, followed by a frequency sweep (0.5 Hz) at 1% strain. The changes in G ′, G ″, and tan δ were recorded during the following 2.5 h …”
Section: Methodsmentioning
confidence: 99%